Brilliant Diatribe - Williams, D. H. (Defending and Defining the Faith: An Introduction to Early Christian Apologetic Literature, 2020)
This chapter considers the work of Tertullian of Carthage. No Christian apologetic author could match Quintus Septimius Florens Tertullianus (Tertullian) in his sardonic rhetorical style and massive erudition when writing against Christian heretics, fellow Catholics, and menacing pagans. His handful of apologetic works represent an apex in the refinement of refuting pagan denigrations of Christianity during the second and third centuries. Most remarkable in Tertullian’s case is that the reader encounters not merely another body of apologetic texts that marshaled philosophical or historical arguments against pagan condemnations, but the invention of a series of related texts advising Christians how they should live in and respond to a hostile culture.
paid